2014
DOI: 10.1111/nous.12064
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge in and out of Contrast

Abstract: We report and discuss the results of a series of experiments that address a contrast effect exhibited by folk judgments about knowledge ascriptions. The contrast effect, which was first reported by Schaffer and Knobe (2012), is an important aspect of our folk epistemology. However, there are competing theoretical accounts of it. We shed light on the various accounts by providing novel empirical data and theoretical considerations. Our key findings are, firstly, that belief ascriptions exhibit a similar contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Previous work has failed to find any evidence that reflection has any influence on philosophical judgment (Weinberg et al, 2012;Gerken and Beebe, 2016;Colaço et al, ms), but only a few cases have been examined. The study reported above extends the assessment of the reflection defense in a new direction.…”
Section: Reflectionmentioning
confidence: 99%
“…Previous work has failed to find any evidence that reflection has any influence on philosophical judgment (Weinberg et al, 2012;Gerken and Beebe, 2016;Colaço et al, ms), but only a few cases have been examined. The study reported above extends the assessment of the reflection defense in a new direction.…”
Section: Reflectionmentioning
confidence: 99%
“…While the most prominently discussed GRECI explanations trace intuitive knowledge‐attributions to a ‘mind‐reading competency’ (e.g. Nagel, ; Boyd & Nagel, ; Alexander et al, ; Gerken & Beebe, ), stereotypical enrichment is a domain‐general language process that can shape intuitions about any topic.…”
Section: Philosophical Relevancementioning
confidence: 99%
“…17 Proponents of this movement seek to develop psychological explanations of our intuitions that can help to assess their evidentiary value. Recent studies in cognitive epistemology develop this approach by first tracing intuitions back to the particular cognitive processes that give rise to them, and then identifying vitiating circumstances in which our intuitions can lead us astray (e.g., Nagel 2010Nagel , 2012bFischer 2014;Alexander et al 2015;Gerken and Beebe 2016;Fischer andEngelhardt 2016, 2017b). Ultimately, the hope is to provide an 'epistemic profile' of the cognitive processes underlying philosophical intuitions that allows us to assess their evidential merit in specific types of philosophical inquiry.…”
Section: Cognitive Epistemologymentioning
confidence: 99%